2015
DOI: 10.1002/jcb.25176
|View full text |Cite
|
Sign up to set email alerts
|

ROS‐Induced Nuclear Translocation of Calpain‐2 Facilitates Cardiomyocyte Apoptosis in Tail‐Suspended Rats

Abstract: Isoproterenol (ISO) induced nuclear translocation of calpain-2 which further increased susceptibility of cardiomyocyte apoptosis in tail-suspended rats. The underlying mechanisms remain elusive. In the present study, the results showed that ISO (10 nM) significantly elevated NADPH oxidases (NOXs) activity and NOXs-derived ROS productions which induced nuclear translocation of calpain-2 in cardiomyocytes of tail-suspended rats. In contrast, the inhibition of NADPH oxidase or cleavage of ROS not only reduced ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Most importantly, the expression and activities of calpain-1/2 were largely inhibited in ligated TG mice. It has been reported that calpastatin overexpression reduces reactive oxygen species (ROS) production and peroxynitrite formation in diabetic mice 44 , and ROS overload is able to enhance the expression and activity of calpains 45 46 47 . Thus, calpastatin induction may not only directly prevent calpains activation, but also indirectly inhibit calpains expression by lessening ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the expression and activities of calpain-1/2 were largely inhibited in ligated TG mice. It has been reported that calpastatin overexpression reduces reactive oxygen species (ROS) production and peroxynitrite formation in diabetic mice 44 , and ROS overload is able to enhance the expression and activity of calpains 45 46 47 . Thus, calpastatin induction may not only directly prevent calpains activation, but also indirectly inhibit calpains expression by lessening ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the reliability of iTRAQ based quantitative analysis, protein samples used for iTRAQ were further examined by western blot which were undertaken as previously described [24]. Briefly, total protein was extracted from the SOL muscle of ground squirrels and solubilized in a sample buffer (100 mM Tris, pH 6.8, 5 % 2-β-mercaptoethanol, 5 % glycerol, 4 % SDS, and bromophenol blue), with muscle protein extracts resolved by SDS-PAGE using Laemmli gels (10 % gel with an acrylamide/bisacrylamide ratio of 37.5 : 1 for EEF-2; and 12 % gel with an acrylamide/bisacrylamide ratio of 29 : 1 for RPS8, proteasome 20S α5, CAPNS1, actin, and troponin C. After electrophoresis, the proteins were electrically transferred to PVDF membranes (0.45 μm pore size) using a Bio-Rad semi-dry transfer apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of cardiomyocyte autophagy leads to the up regulation of the proteolytic factor calpain. Up regulation of ROS in cardiomyocytes induced the nuclear translocation of calpain2 and inhibition of NOX function resisted calpain 2 translocation [104]. Myocardial infarction models show that overexpression of human TFAM in mice mitigates cardiac dysfunction and increases mtDNA copy number [105].…”
Section: Protease Regulationmentioning
confidence: 99%